Optimisation of cat neutering anaesthesia protocols for use in the community - Holgate, Albert Charles Peter (2021)
The aim of this study was to compare the two opioids methadone and buprenorphine in sedative combinations administered to cats undergoing castration in a high-volume neutering setting. Both combinations were used prior to orchidectomy in cats (Routine Cat Castrations) as part of a ‘drop-in clinic’ with no prior appointments required. The overall outcome was to determine a combination to best enable a safe, quick, effective turnover of neuters with limited financial, infrastructure and staffing resources.